Upaya Meningkatkan Kemampuan Kognitif Anak Melalui Bermain Aquarium - Arsy (Program Studi Pendidikan Islam Anak Usia Dini, 2025)
This research uses aquarium media to improve children???a cognitive abilities. The aim of this research is to determine the cognitive development of children aged 4-5 years at TK Pratiwi Indralaya and cognitive improvemenr through aquarium play at TK Pratiwi Indralaya. The research subjects were class A children of TK Pratiwi Indralaya a total of 20 children. The research results showed a significant increase in the ability to recognize numbers 1-5 80% based on the evaluation of the results from the first and second stages.